Whose region is it? A few words on a certain research project and Silesian history - Wiszewski, Przemysław (Wydawnictwo eBooki.com.pl, 2013)
This collection of articles represents the output of the first stage of research on the history of the region of Silesia, conducted under the patronage of the European Science Foundation as part of the project ‘Cuius regio. An analysis of the cohesive and disruptive forces determining the attachment and commitment of (groups of) persons to and cohesion within regions’. Silesia, one of the regions analyzed in the project, is an example of a borderland territory whose historical development was substantially influenced by various cultural traditions. The primary goal of the research on the Silesian history was to determine the factors that led to disintegration and subsequent re-creation of the region, for there are arguments indicating that the history of the local community has been – and continues to be – the product of a dynamic process whose course was not determined solely by the factor of its constant existence within the limits demarcated within the 16th-century Kingdom of Bohemia. We are hopeful that the book will inspire a discussion in the academic community on a new dimension of the social history of Silesia, on issues connected with the development of Europe’s regions and on universal mechanisms present in the formation of regional social cohesion.
Keywords: Opolszczyzna; Śląsk; historia regionalna; historia społeczna; spójność społeczna